2021
DOI: 10.1101/2021.03.22.436441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of the second SARS-CoV-2 mRNA vaccine dose on T cell immunity in naïve and COVID-19 recovered individuals

Abstract: The rapid development and deployment of mRNA-based vaccines against the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) led to the design of accelerated vaccination schedules that have been extremely effective in naive individuals. While a two-dose immunization regimen with the BNT162b2 vaccine has been demonstrated to provide a 95% efficacy in naive individuals, the effects of the second vaccine dose in individuals who have previously recovered from natural SARS-CoV-2 infection has been questione… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 13 publications
6
25
0
1
Order By: Relevance
“…Our study provides evidence for an early, stronger and more durable immune response in Covid-19 experienced HCWs vs. naïve HCWs after vaccination with the BNT162b2 mRNA vaccine. An early and strong response of a similar order of magnitude has been described after the first dose of the vaccine in previous studies in experienced individuals 4,5,6,7,8,9 . It is important to note that this early and strong response was also shown by experienced HCWs who were negative for anti-SARS-CoV-2 antibodies prior to receiving the first dose of the BNT162b2 vaccine.…”
Section: Discussionsupporting
confidence: 76%
“…Our study provides evidence for an early, stronger and more durable immune response in Covid-19 experienced HCWs vs. naïve HCWs after vaccination with the BNT162b2 mRNA vaccine. An early and strong response of a similar order of magnitude has been described after the first dose of the vaccine in previous studies in experienced individuals 4,5,6,7,8,9 . It is important to note that this early and strong response was also shown by experienced HCWs who were negative for anti-SARS-CoV-2 antibodies prior to receiving the first dose of the BNT162b2 vaccine.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, in contrast to controls, a decrease in the frequency of SARS-CoV-2 S-reactive IFN-g T cells, most notably CD4 þ T cells, was noticed in post-vaccination specimens from most nursing-home residents, regardless of their SARS-CoV-2 infection status. Interpreting the T-cell response data presented herein is confounded by difficulty in ascertaining the true infection status of participants, regarding which a differential effect of the second Comirnaty dose on T-and B-cell immunity was reported in COVID-19-naïve and recovered individuals, with the latter exhibiting poorer responses [16,17], perhaps due to the development of immunological anergy. These observations [16,17], if confirmed, would lend support to the use of a single booster dose for previously infected individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Interpreting the T-cell response data presented herein is confounded by difficulty in ascertaining the true infection status of participants, regarding which a differential effect of the second Comirnaty dose on T-and B-cell immunity was reported in COVID-19-naïve and recovered individuals, with the latter exhibiting poorer responses [16,17], perhaps due to the development of immunological anergy. These observations [16,17], if confirmed, would lend support to the use of a single booster dose for previously infected individuals. In effect, functional SARS-CoV-2 S IFN-g T cells detected in prevaccination specimens may well have been seasonal coronavirus cross-reactive T cells (see [18] for a review).…”
Section: Discussionmentioning
confidence: 98%
“…Earlier phase III trials and more recent studies have demonstrated that both mRNAbased vaccines induce a strong anti-S IgG humoral response and promote the generation of S-specific memory T and B cells after the two-dose regimen [2][3][4][5][6][7][8] . Among the different antibodies induced upon vaccination, the ones that specifically recognize the receptor binding domain (RBD) of the viral S protein are particularly relevant as they mirror the neutralizing capacity of the sera 9,10 and are considered a principal surrogate of immune protection and vaccine efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, recent studies have shown that SARS-CoV-2 naïve individuals and individuals with prior history of infection have distinct immune responses upon mRNA vaccination. Following the first vaccine dose, COVID-19 recovered individuals show significantly higher S-and RBD-specific IgG titers, superior serum neutralization activity 7,[11][12][13] , even against SARS-CoV-2 variants 8,14,15 , and increased S protein-specific memory T and B cell responses than naïve individuals [4][5][6]14 . This enhanced response is consistent with the persistence of humoral and cellular immunity against SARS-CoV-2 in convalescent individuals, as previously reported [16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%